Deskripsi Kemampuan Berpikir Kreatif Dalam Mengerjakan Soal Pemecahan Masalah Ditinjau dari Gaya Kognitif Siswa Kelas VIII SMPN 13 Mataram - Sabrina, Annisa; Sarjana, Ketut; Lu’luilmaknun, Ulfa (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The purpose of this study was to describe students’ creative thinking skills in solving problem-solving questions in terms of cognitive style of eighth-grade students at SMPN 13 Mataram. A qualitative research method was used with descriptive approach. Three instruments were used in this study, GEFT test question to determine student cognitive style, math question in the form of description questions on the material of Polyhedron, and interview guidelines. The subjects were chosen using purposive sampling and involved 6 students, with 3 students representing each cognitive style selected based on GEFT test. subsequently, a creative thinking skills test was administered, followed by a semi-structured interview to confirm the students’ creative thinking abilities. The data analysis technique used Miles and Hubermans, interactive analysis model, while data credibility was tested using technique triangulation. The results of the study showed that one subject with a field-dependent cognitive style did not meet any of the three indicators of creative thinking skills, two field-dependent subjects met the fluency indicators, two field independent subjects met the fluency and flexibility indicators, and one field independent subject met all three indicators of creative thinking skills.